PENGARUH KUALITAS PRODUK, HARGA, PROMOSI, DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN RUMAH - EKA SRIWAHYUNI; TIN AGUSTINA KARNAWATI; WIDI DEWI R (AKADEMIKA, 2022)
The purpose of this research is to find out and analyze; 1) the influence of product quality on home buying decisions, 2) the effect of price on home buying decisions, 3) the effect of promotion on home buying decisions, 4) the effect of housing location on home buying decisions, and 5) the influence of product quality, price, promotion, and housing location simultaneously on home buying decisions. This type of research is explanatory research with a survey approach. This research was conducted on people who bought a house in the Patraland Place Housing Area, Malang City. The sample in this study amounted to 122 respondents with purposive sampling technique. The results showed 1) there was an insignificant effect of product quality on home buying decisions, 2) there was a significant effect of price on home buying decisions, 3) there was a significant effect of promotion on home buying decisions, 4) there was a significant influence of housing location on home buying decisions. , and 4) there is a significant effect of product quality, price, promotion, and housing location simultaneously on home buying decisions.